1999
DOI: 10.1007/s002239900641
|View full text |Cite
|
Sign up to set email alerts
|

Meltrin-α, a Fusion Protein Involved in Multinucleated Giant Cell and Osteoclast Formation

Abstract: The formation of multinucleated cells such as myotubes, macrophage-derived giant cells (MGC), and osteoclasts is the result of cell-cell fusion of mononuclear precursors. Meltrin-alpha, -beta, and -gamma are members of a recently discovered family of proteins that contain disintegrin and metalloprotease domains and are related to fertilin, a protein involved in egg-sperm fusion. Based on this and evidence implicating meltrin-alpha in myoblast formation, we have investigated the possibility that meltrins may al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 29 publications
3
68
1
Order By: Relevance
“…In a recent study, Abe et al (1999) demonstrated that antisense oligonucleotides of meltrin involved in eggsperm fusion inhibited by 70% the formation of multinucleated osteoclast-like cells expressing TRAP in co-cultures of bone marrow cells. Moreover, anti-fusion regulatory protein-1/CD98 antibody has been shown to induce stimulated multinucleated giant cell and osteoclast formation (Higuchi et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Abe et al (1999) demonstrated that antisense oligonucleotides of meltrin involved in eggsperm fusion inhibited by 70% the formation of multinucleated osteoclast-like cells expressing TRAP in co-cultures of bone marrow cells. Moreover, anti-fusion regulatory protein-1/CD98 antibody has been shown to induce stimulated multinucleated giant cell and osteoclast formation (Higuchi et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…(13) Therefore, although the functions of osteoclasts and FBGCs differ, they express common molecules, such as DC-STAMP, that function in cell-cell fusion. (3) To date, various molecules have been identified that regulate fusion of osteoclasts or macrophages, including DC-STAMP, ATP6v0d2, CD47, CD44, CD9, CD81, MFR, E-cadherin, and meltrin-a (3,(14)(15)(16)(17)(18)(19)(20)(21) ATP6v0d2-deficient mice show significant reductions in fusion of either cell type. (21) DC-STAMP-deficient osteoclasts or FBGCs show a complete lack of cell-cell fusion, a function specific for macrophage lineage fusion, since fertilization and myotube formation is normal in DC-STAMP-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…Although the MGCs seen in CGCG share some similarities with the osteoclast 26,27 , there are enough phenotypic differences to suggest that these may not be true osteoclasts 28 . It is generally accepted that these MGCs develop as a result of cell-cell fusion of mononuclear cells 29 . Possible origins of these mononuclear cells include endothelial cells 30 , myofibroblasts 31 with Noonan syndrome.…”
Section: Introductionmentioning
confidence: 99%